ASUHAN KEPERAWATAN KELUARGA IBU E DENGAN GOUT ARTHRITIS DI RT 04 RW 07 KELURAHAN LIMO KOTA DEPOK - Aziza Aziz (2023)
Elderly with changes in the musculoskeletal system, one example is gout arthritis, gout arthritis if left untreated can cause joint damage, which over time changes the joint structure, overcomes joint function and eventually paralyzes, making it difficult for patients to carry out daily activities (Sari, 2016) . The purpose of this study was to provide nursing care to Mrs. E's family with Gout Arthritis in Rt 04 Rw 07 Limo Village, Limo District, Depok City. The research design used by descriptive research researchers with a case study approach. The results of this study found family nursing diagnoses in Mrs. E's family, namely ineffective health management and readiness to increase knowledge. While the interventions carried out are adjusted to 5 family health tasks. Evaluation of the results obtained from these diagnoses, namely ineffective health management and readiness to increase knowledge can be overcome. From the cases found in patients, it was found that there was a difference between theory and cases during implementation in the field, this was described in nursing diagnoses while in nursing assessment, nursing intervention, nursing implementation and nursing evaluation, there was no difference between theory and cases. It is hoped that the provision of family nursing care can increase the knowledge and ability of the family in caring for patients with gouty arthritis.